Pemberdayaan Kader Sebaya Dalam Pencegahan TB Di Desa Bone Kecamatan Nekamese Kabupaten Kupang - Ni Made Susilawati; Neiny Prisy Foekh; Meliance Bria (Jurnal Kabar Masyarakat, 2023)
Tuberculosis (TB) is one of the ten causes of death in the world. This disease is a chronic infectious disease caused by Mycobacterium tuberculosis. Indonesia ranks third in the world in terms of TB sufferers, after India and China. Kupang Regency is a contributor to tuberculosis cases in East Nusa Tenggara and Nekamese District, one of which is that the incidence rate is still quite high. Knowledge about symptoms, transmission and treatment of disease among the community, especially teenagers, is still lacking with TB cases still being found. Empowering teenagers as health drivers is expected to be able to increase public awareness, especially teenagers, regarding prevention, symptom monitoring and discovery and treatment of tuberculosis. Tuberculosis education can increase adolescent knowledge, so that adolescents know the importance of maintaining a clean and healthy lifestyle so that TB transmission can be reduced. This community service activity is carried out to contribute to improving youth's knowledge and attitudes about pulmonary TB through comprehensive TB counseling by providing structured information about pulmonary TB and empowering teenagers by strengthening agents of change (peer cadres in the health sector) and monitoring in the community who have symptoms of tuberculosis, especially in children. The results of the activity showed an increasingly better level of understanding among teenagers about TB disease from 35% to 85%. At the monitoring stage in the community, especially teenagers, no symptoms of tuberculosis were found and all were in good health. It is hoped that in the future peer cadres (adolescents) will be able to adopt a clean and healthy lifestyle and become pioneers in monitoring tuberculosis symptoms in the community so that they are easier to find and receive treatment/treatment quickly. Peer cadres can practice Clean and Healthy Living Behavior so they are able to transfer information about Pulmonary TB to the community, especially teenagers.